(Invited) Heterogeneous Photonic Integration by Direct Wafer Bonding. (24th August 2016) - Davenport, Michael L; Chang, Lin; Huang, Duanni; Volet, Nicolas; Bowers, John E
Abstract : Direct wafer bonding is a powerful technique for combiningsemiconductor materials that cannot normally be monolithicallyintegrated. It allows combination of heterogeneous materials withdifferent properties onto a single substrate, enabling the productionlarge scale and multi-functional photonic circuits.